2013
DOI: 10.1007/s13244-012-0214-8
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral analysis of the cross-sectional area of the internal mammary arteries and veins in patients with and without breast cancer on breast magnetic resonance imaging

Abstract: ObjectiveTo analyse bilateral differences in the cross-sectional area of the internal mammary artery (IMA) and vein (IMV) in breast cancer patients compared to healthy controls.Materials and methodsOn 135 breast MRIs the cross-sectional areas of the IMA and IMV were measured on the left and right side in the second and third intercostal space (ICS) by two independent readers. Differences were analysed using a linear mixed model.ResultsIn the healthy control group (n = 91) no significant differences between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…In a study carried out by Schipper et al (13) in 2012, diameters were measured as in our study. Their study differs from ours in measurements being made of the IMA diameter before reaching the breast through the intercostal space, not considering LTA diameters, and including only malignant lesions in the study.…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out by Schipper et al (13) in 2012, diameters were measured as in our study. Their study differs from ours in measurements being made of the IMA diameter before reaching the breast through the intercostal space, not considering LTA diameters, and including only malignant lesions in the study.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study Schipper et al (2013) found that the vascular cross-sectional area of the internal mammary vessels is significantly larger on the side with breast cancer compared to the contralateral side. This chapter investigates the veracity of this finding.…”
Section: Summary and Conclusion 118mentioning
confidence: 94%
“…The next section reviews the study of Schipper et al (2013). Section 6.2 then proffers a new method for the automatic detection and measurement of the internal mammary vessels.…”
Section: Summary and Conclusion 118mentioning
confidence: 99%
See 2 more Smart Citations